THE RELATIONSHIP OF MOTHER'S KNOWLEDGE WITH EARLY BREASTFEEDING FOR BABIES IN SIALAMAN VILLAGE, SIPIROK DISTRICT, TAPANULI SELATAN REGENCY IN 2020: THE RELATIONSHIP OF MOTHER'S KNOWLEDGE WITH EARLY BREASTFEEDING FOR BABIES IN SIALAMAN VILLAGE, SIPIROK DISTRICT, TAPANULI SELATAN REGENCY IN 2020 - MKM, Masnawati (Universitas Aufa Royhan, 2021)
Giving complementary foods with breast milk too early in infants aged less than six months can have an impact on the baby's health, including flatulence, diarrhea, constipation and even food allergies, the cause of this is the baby's digestive system is not ready to receive food other than breast milk, causing a reaction in the baby's digestive system. The purpose of the study was to determine the relationship between mother's knowledge and early complementary feeding to infants in Sialaman village, Sipirok district, Tapanuli Selatan regency in 2021. This study was a correlation analytic study with a cross sectional approach. The population is all mothers who have babies totaling 44 people and all of them are used as samples. The results showed that there was a significant relationship between mother's knowledge and early complementary feeding to infants with p value = 0.002 < = 0.05. For mothers who have babies aged < 6 months to give only breast milk and give complementary foods appropriately and avoid giving formula milk and other food/drinks. For mothers who have babies aged > 6 months to give the right complementary foods with breast milk to the baby. It is recommended to health workers to be more active in providing health education to the community, especially to mothers who have babies about exclusive breastfeeding and giving the right complementary foods with breast milk to babies.